Получение композиционных материалов на основе поли-ɛ-капролактона и модифицированного гидроксиапатита - Карасева, Светлана Александровна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XVIII Международной конференции студентов, аспирантов и молодых ученых, 27-30 апреля 2021 г.)
In this study hydroxyapatite modified with citric acid was obtained. The chemical and functional composition of the modified hydroxyapatite was studied by IR-spectroscopy. A polymerization catalyst based on modified hydroxyapatite and tin chloride was obtained. In situ polymerization was carried out with the resulting catalyst to obtain a composite material.